2001
DOI: 10.1128/cdli.8.6.1136-1139.2001
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization with Milk Produced from an Immunized Cow Prevents Oral Recolonization by Streptococcus mutans

Abstract: Cell surface protein antigen (PAc) and water-insoluble glucan-synthesizing enzyme (GTF-I) produced by cariogenic Streptococcus mutans are two major factors implicated in the colonization of the human oral cavity by this bacterium. We examined the effect of bovine milk, produced after immunization with a fusion protein of functional domains of these proteins, on the recolonization of S. mutans. To prepare immune milk, a pregnant Holstein cow was immunized with the fusion protein PAcA-GB, a fusion of the saliva-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…These results support the importance of inducing salivary responses that could interfere with the two different stages involved in the pathogenesis of S. mutans infection (i.e., attachment to and accumulation on tooth surfaces) in developing a vaccine against dental caries. Recent studies by others using a similar fusion protein, termed "PAcA-GB," have shown that bovine milk containing antibodies against the fusion protein was effective in controlling the recolonization of S. mutans in the oral cavity of humans (37). Furthermore, passive immunization of rats with bovine milk containing antibodies against the PAcA-GB fusion protein was shown to protect against S. mutans induced dental caries in a rat model (25).…”
Section: Discussionmentioning
confidence: 99%
“…These results support the importance of inducing salivary responses that could interfere with the two different stages involved in the pathogenesis of S. mutans infection (i.e., attachment to and accumulation on tooth surfaces) in developing a vaccine against dental caries. Recent studies by others using a similar fusion protein, termed "PAcA-GB," have shown that bovine milk containing antibodies against the fusion protein was effective in controlling the recolonization of S. mutans in the oral cavity of humans (37). Furthermore, passive immunization of rats with bovine milk containing antibodies against the PAcA-GB fusion protein was shown to protect against S. mutans induced dental caries in a rat model (25).…”
Section: Discussionmentioning
confidence: 99%
“…There are also data to show that passive immunization in humans impedes recolonization of selected target micro-organisms in both caries (Koga et al, 2002;Smith, 2002) and periodontal disease (Booth et al, 1996). As vehicles for passive immunization, both milk from immunized cows (Shimazaki et al, 2001) and transgenic plants (Ma et al, 1998) have been tested, with encouraging results. Likewise, chimeric recombinant microbial vectors that are avirulent but which express antigens from S. mutans (Huang et al, 2001;Taubman et al, 2001) or P. gingivalis (Sharma et al, 2001) have been shown to provide protection against dental caries and alveolar bone loss, respectively, in experimental animals.…”
Section: (323) Immunizationmentioning
confidence: 99%
“…The vehicles for passive immunization, such as milk from immunized cows (Shimazaki et al, 2001) and transgenic plants (Ma et al, 1998), have been tested with promising results. Similarly, it was shown that recombinant chimeric microbial vectors that are non-virulent, but express antigens of S. mutans (Huang et al, 2001, Taubman et al, 2001 or P. gingivalis (Sharma et al, 2001) promoted protection against tooth decay and loss of alveolar bone in experimental animals.…”
Section: Recent Advances In Anti-plaque Agents: Chemoprophylactic Agementioning
confidence: 99%